Application of Culturally Responsive Teaching Through the Piil Pesenggiri Philosophy to Enhance Learning Outcomes and Cultural Interest in PKn for Fourth Grade of Elementary Students - Muadz Assidiqi; Sutarmi Sutarmi (Universitas Sebelas Maret, 2024)
By implementing culturally responsive teaching practices, the research aims to improve learning outcomes and foster cultural interest among fourth-grade elementary students in PKn. The problem in this study is the students' lack of cultural understanding, which leads to their ignorance of the cultural values present in their surroundings, particularly Piil Pesenggiri. This study employed the class action research method in one of the elementary schools in Lampung. The phases of this research consist of five stages, as follows: action planning, action implementation, observation, reflection, and evaluation. Research instruments consist of interview questions, issues, and cultural interest-raising. This research employed an interactive analysis approach. The pre-cycle results revealed a low level of student cultural interest, with a 70% achievement percentage, a 75% teacher learning activity, and an average percentage of 72.5%. Furthermore, Cycle I results were 78.84% for teacher activity and 75% for student activity, with a total Cycle I percentage of 76.92%. The teacher activity results were 94.23%, the student activity was 91.66%, and the total percentage in Cycle II was 92.95%. Furthermore, the breakdown of student learning outcomes by cycle is as follows: 12.50% had an average of 52.38 for pre-cycles, 59.09% had an average of 62.27 for cycles I, and 90.90% had an average of 81.13 in cycles II. Based on these findings, we can conclude that incorporating Piil Pesenggiri's philosophical values into culturally responsive teaching can help students learn more about their own and other cultures and become more interested in PKn. It is hoped that the findings of this research can contribute to knowledge related to culturally responsive learning about the spirit of nationalism and fostering inter-ethnic tolerance as a basis for further research, such as R&D